BIODEGRADASI BAHAN ORGANIK OLEH MIKROBA DAN PENGARUHNYA TERHADAP TANAMAN PADI DI LAHAN GAMBUT - - Mukhlis (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2014)
Organic matter as a source of organic fertilizer is very useful to increase agricultural production, decrease environmental pollutants, and increase land quality. This research aims to understand the roles of microbes on organic degradation and the effects on paddy plant in peat land. The research was conducted in the peat land of Liang Anggang village, Landasan Ulin subdistrict, Banjarbaru District, South Kalimantan province in the dry season 2010. There were two steps of experiment, i.e: (1) degradation of organic matter (composting) by using biodecomposer Mdec (consortia of decomposer microbes) and Trichoderma; (2) effects of biocompost on paddy plant. Treatments were biocompost (Mdec), biocompost (Trichoderma), and without compost (farmer’s method) and arranged by using a randomized completely block design with five replications. Research results showed that biocompost quality made by using Mdec was better than that of Trichoderma degraded one. Composting process using Mdec decreased C/N ratio from 43.32 to 17.30 within two weeks. At the same time, C/N ratio of biocompost made by using Trichoderma was still high (35.00). Biocompost (Mdec) gave the highest paddy yield (3.50 t/ha), while biocompost (Trichoderma) and no compost treatments gave paddy yield as much as 3.32 t/ha and 2.96 t/ha respectively.